12(n-4)=

Simple and best practice solution for 12(n-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(n-4)= equation:


Simplifying
12(n + -4) = 0

Reorder the terms:
12(-4 + n) = 0
(-4 * 12 + n * 12) = 0
(-48 + 12n) = 0

Solving
-48 + 12n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + 12n = 0 + 48

Combine like terms: -48 + 48 = 0
0 + 12n = 0 + 48
12n = 0 + 48

Combine like terms: 0 + 48 = 48
12n = 48

Divide each side by '12'.
n = 4

Simplifying
n = 4

See similar equations:

| 7=-8u+3(u+4) | | 4n^2-11n-119=0 | | 2k+11=31 | | 2(4x+4)=-5(3x-2) | | 4x-7(-x-13)=25 | | 617252.2592=2604.4416*H | | 6c-4c-c=12 | | 4r^2+20r+14=-2 | | 4f-3=23 | | 5h-16=-6+6h | | x/1.3-8.1=11.9 | | 4s+2s-2s-3s=10 | | 4.6x-63.5=22.1 | | 5s-17s-7s-18s-8s=-15 | | 19h-17h-h=9 | | tan70=9/x | | X=(156-9y)/5 | | 11c+3c-14c+2c=16 | | 3y-19y=-16 | | G=10log(x) | | 20m-m-10m=18 | | -68=-4x+6(2x-2) | | G=10logx | | 0=-16x^2+32x-17 | | 9(3/5)^2x=999 | | Vx-7=3-X | | 7cos^2x-cosx-8=0 | | -4=x/2=6 | | 105=-2x+5(7x-12) | | 20x+5=-6x+12 | | -5x+1=-2 | | (3+x)*3=9 |

Equations solver categories